Extended Distribution of Critically Endangered Crinum woodrowii (Family Amaryllidaceae) to Gujarat, India - Kambale, Sharad; Chaudhari, Ashok; Gangurde, Ajay; Bhusare, Dipak; Gholave, Avinash; Adsul, Avinash; Gosavi, Kumar Vinod C. (Journal of the Bombay Natural History Society (JBNHS), 2026)
No Abstract.